Characteristics associated with quality of life in the early stages of Mycosis Fungoides - Pedram Nourmohammadpour; Maryam Nasimi; Zeinab Aryanian; Azadeh Goodarzi; Reyhaneh Jahazi; Ifa Etesami (Babol University of Medical Sciences, 2023)
Background: Mycosis fungoides (MF) is a lymphoproliferative disorder characterized by skin-homing atypical lymphocytes. This study aimed to evaluate the quality of life (QoL) in MF patients in the early stages of the disease and the associated factors using the Dermatology Life Quality Index (DLQI). Methods: Thirty MF patients (21 females/9 males) with a mean age of 46.73±15.9 years and in the early stages of the disease (26 stage Ι and 4 stage ΙΙ) were enrolled and were asked to fill the DLQI questionnaire. Results: The mean DLQI score was 9.93±5.89. The QoL was largely affected by the disease in near half of the patients (46.7% of patients had a DLQI score11-20). QoL was significantly correlated with educational level and was more impaired in patients with lower educational status (DLQI score spearman rho=-0.382, P=0.037). QoL was not associated with sex, age, disease stage and disease duration. The symptom and feeling dimension of DLQI was significantly more impaired in patients with both patch and plaque compared to patch only (spearman rho= 0.397, P= 0.03). Conclusion: This study demonstrates how largely patients' QoL is influenced in the early stages of MF, especially in patients with lower educational levels.